2020
DOI: 10.1016/j.neuroimage.2019.116122
|View full text |Cite
|
Sign up to set email alerts
|

Sex-biased trajectories of amygdalo-hippocampal morphology change over human development

Abstract: The amygdala and hippocampus are two adjacent allocortical structures implicated in sex-biased and developmentally-emergent psychopathology. However, the spatiotemporal dynamics of amygdalo-hippocampal development remain poorly understood in healthy humans. The current study defined trajectories of volume and shape change for the amygdala and hippocampus by applying a multi-atlas segmentation pipeline (MAGeT-Brain) and semi-parametric mixed-effects spline modeling to 1,529 longitudinally-acquired structural MR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…However, future research that is designed to investigate cortisol as a mediating factor linking metals exposure with neurodevelopmental outcomes is of interest and would contribute to the field. Other research has shown significant sex differences in amygdala growth trajectories 103 , 104 and activity in response to novel and fearful stimuli. 105 110 In the present study, we found that girls displayed more fearful behaviors compared with boys and that the divergence in scores increased with increasing metals exposure.…”
Section: Discussionmentioning
confidence: 94%
“…However, future research that is designed to investigate cortisol as a mediating factor linking metals exposure with neurodevelopmental outcomes is of interest and would contribute to the field. Other research has shown significant sex differences in amygdala growth trajectories 103 , 104 and activity in response to novel and fearful stimuli. 105 110 In the present study, we found that girls displayed more fearful behaviors compared with boys and that the divergence in scores increased with increasing metals exposure.…”
Section: Discussionmentioning
confidence: 94%
“…Participants were recruited from Shenzhen University through online and public postings. All postings specified the inclusion criteria of the study: (i) male [to control sex effect on cortisol response ( Liu et al ., 2019 ) and sex-based differences in the development of the hippocampus and amygdala ( Fish et al., 2020 )]; (ii) normal hearing ability and physically healthy; (iii) no habit of staying up late and (iv) no psychiatric disorders including depression, etc. All eligible participants were further screened by the following exclusion criteria: (i) history of psychiatric or neurological disease, epilepsy or migraine; (ii) history of endocrine disorders (such as Cushing’s syndrome); (iii) history of other major chronic physiological diseases, such as diabetes, heart disease, meningitis, severe kidney disease and malignant tumors; (iv) history of brain injury (such as brain surgery, cerebral hemorrhage and severe head trauma); (v) long-term use of antipsychotic, neurological or adrenocortical hormone drugs; (vi) long-term use of other medications; (vii) major operation in the past 6 months; and (viii) smoking (more than five cigarettes a day) and drinking habit (more than two alcoholic drinks daily).…”
Section: Methodsmentioning
confidence: 99%
“…Among other policy-relevant results, the price of starred foods relative to unstarred foods was negatively associated with nutritional quality. This is consistent with the law of demand-a tenet of economics that predicts demand to increase in response to a decline in price [42]. As starred foods become more expensive relative to unstarred foods, the mix of purchase shifts toward unstarred foods and, hence, causes a reduction in nutritional quality.…”
Section: Discussionsupporting
confidence: 82%